EFEKTIVITAS FUMIGAN ALUMINIUM FOSFIDA TERHADAP Rhyzoperta dominica PADA BERAS DI GUDANG PERUM BULOG KUPANG, NUSA TENGGARA TIMUR - Ariesta P. Sesfao; Jesayas A. Londingkene; Petronella S. Nenotek (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
This research was carried out at the Perum Kupang Warehouse, East Nusa Tenggara with aimed to determine the effectiveness of aluminum phosphide in controlling Rhyzoperta dominica in the Bulog Perum warehouse. This study was arranged in a completely randomized design (CRD) method with 5 treatment doses and each treatment was repeated five times. The variables observed were mortality symptoms of R. dominica, mortality of R. dominica treated with aluminum phosphide and rice loss. The results showed that the mortality of R. dominica treated with aluminum phosphide showed symptoms of body shrinkage as it gradually dried and became stiffer. Aluminum phosphide fumigant was toxic to R. dominica imago and each treatment had different level of toxicity. At doses of 8 g ton-1 and 18 g ton-1 of Aluminum phosphide fumigant, it could kill R. dominica imago ≥95%. The results of probit analysis showed that aluminum phosphide could kill 50% of the tested insects at a dose of 6.33 g ton-1 (LD50) and 18.37 g ton-1 (LD90) at one week after treatment (WAT), while at four WAT, at a dose of 1.28 g ton-1 (LD50) and 8 g ton-1 aluminum phosphide could kill 50% and 95% of insects tested, respectively. There was no rice shrinkage observed in each treatment, this is presumably because on the first day of weighing R. dominica imago had been exposed to phosphine gas and at one WAT the insects were removed from the sample sack and then transferred to a new container to observe weekly mortality.